PENGARUH STRATEGIC MANAGEMENT ACCOUNTING, SUPPLY CHAIN PERFORMANCE DAN CUSTOMER VALUE PADA FIRM FINANCIAL PERFORMANCE - M. Farian Thaib I.; Unggul Purwohedi; Diah Armeliza (Transpublika Publisher, 2023)
Indonesia is one of the countries in Southeast Asia with a high GDP. However, Indonesia's logistic performance is not very impressive, ranking 46th out of 160 countries with an index of 3.15, still falling behind Singapore, Thailand, and Malaysia. This phenomenon could be attributed to a lack of supply chain configuration. Supply chain management involves how firms manage their resources as inputs, which are then processed to become products or outputs. Furthermore, in the field of strategic management, researchers have noted that firms in emerging countries are increasingly moving away from strategic management accounting (SMA), primarily due to its high cost and the need for experts to conduct SMA. However, it's worth noting that SMA includes supply chain configuration as a means to reduce costs and improve efficiency. SMA is not just about managing costs; it also focuses on enhancing performance from the customer's perspective, emphasizing Customer Value. Customer Value is a technique for boosting a firm's performance by strengthening customer relationships. Given the limited research in emerging countries, especially in Indonesia, this topic warrants further investigation. This research aims to analyze the effects of strategic management accounting, supply chain performance, and Customer Value on a firm's financial performance. Using a quantitative approach (SEM-PLS), 100 samples from Small and Medium Enterprises (SMEs) in Kota Bogor were tested. The results indicate that strategic management accounting has a negative effect on Firm Financial Performance, while Supply Chain Performance and Customer Value have positive effects on Firm Financial Performance.